1998
DOI: 10.1021/la980825a
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Electrochemical Quartz Crystal Microbalance Study of Potential Oscillations during the Electrodeposition of Cu/Cu2O Layered Nanostructures

Abstract: Application of a constant cathodic current to an electrode in an alkaline Cu(II) lactate solution results in oscillation of the electrode potential during the electrodeposition of copper/cuprous oxide layered nanostructures. The electrochemical quartz crystal microbalance (EQCM) is used for in situ phase analysis measurements of the nanoscale layers and the results are compared with bulk XRD measurements. The EQCM is also used to estimate the layer thicknesses and overall modulation wavelength of the nanostruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 22 publications
6
110
1
4
Order By: Relevance
“…Commercially available have previously used electrodeposition to create 9-MHz AT-cut quartz crystals (Seiko EG and G superlattices of metal oxides [14][15][16] and nonequilmodel QA-AM9-AU) were used as the working ibrium layered nanostructures of Cu,0 and Cu which electrode during electrochemical quartz crystal mishowed quantum confinement effects in electrical crobalance (EQCM) experiments. The quartz crystals properties [17][18][19][20][21]. Recently, we reported that epihave a coating on both sides consisting of a 500 A Ti taxial films of 8-Bi 2 03 can be electrodeposited on layer beneath a 3000 A layer of Au.…”
mentioning
confidence: 99%
“…Commercially available have previously used electrodeposition to create 9-MHz AT-cut quartz crystals (Seiko EG and G superlattices of metal oxides [14][15][16] and nonequilmodel QA-AM9-AU) were used as the working ibrium layered nanostructures of Cu,0 and Cu which electrode during electrochemical quartz crystal mishowed quantum confinement effects in electrical crobalance (EQCM) experiments. The quartz crystals properties [17][18][19][20][21]. Recently, we reported that epihave a coating on both sides consisting of a 500 A Ti taxial films of 8-Bi 2 03 can be electrodeposited on layer beneath a 3000 A layer of Au.…”
mentioning
confidence: 99%
“…26 Maximum growth rate is obtained at −1,1 V. The calculated mean values of film thicknesses are 0.62, 0.77, 4.60 and 1.26 μm for the samples 1-4, respectively. Although the deposition potential has an increment of −0.1 V, the film thicknesses do not increase with the same proportion.…”
Section: Resultsmentioning
confidence: 81%
“…[18][19][20] It is thus well known that Cu 2 O is electrodeposited during the positive-going spikes in potential, while Cu and Cu 2 O composite is electrodeposited during the negative-going excursions. adjusted to 9.0 using a 5 M NaOH solution.…”
Section: Resultsmentioning
confidence: 99%